Characteristics of emergency patients with markedly elevated D-dimer levels - Tang, Ning; Pan, Yinyin; Xu, Chao; Li, Dengju (Scientific reports, 2020)
Background: Markedly elevated D-dimer levels can occur in emergency patients with various clinical situations, and is likely to indicate the presence of coagulopathy, rapid differential diagnosis was crucial for them. Methods: D-dimer was detected in consecutive 813 patients entering the emergency department of our hospital, for the patients with D-dimer levels above 5.0 µg/mL, the final diagnoses and 28-day mortality were confirmed, and the levels of thrombomodulin (TM), thrombin-antithrombin complex (TAT) and plasmin-antiplasmin complex (PAP) on admission were detected. Results: There were 148 emergency patients with D-dimer levels higher than 5.0 µg/mL mainly due to sepsis, malignancy, trauma, venous thromboembolism (VTE), cerebrovascular accident, and so on. Both of the TM and TAT levels among these diagnoses were significantly different ( p < 0.001). The elevated TM (>13.3 TU/mL) had a predictive value of 96.0% for excluding VTE, and the normal TM had a predictive value of 90.4% for excluding sepsis. The overall 28-day mortality of these patients with D-dimer >5.0 ug/mL was 14.2%, the TAT level on admission was independently associated with 28-day mortality (odds ratio 1.014, 95% CI 1.001–1.027, P = 0.030). Conclusions: The medical emergencies associated with markedly elevated D-dimer levels were revealed, specific markers of endothelial dysfunction and thrombin generation measured by automatic analyzer have the potential to distinguish diagnoses and predict outcomes in these patients.